DAMPAK REVITALISASI KAWASAN PELABUHAN DONGGALA TERHADAP KESEJAHTERAAN MASYARAKAT SEKITAR - Subagiyo, Subagiyo (Katalogis, 2017)
This study aims to: (1) Examine the impact of the revitalization of the Donggala port to the development of the region over the last 3 years (2) Examine the impact of Donggala port revitalization in the welfare of the surrounding community. The sample in this study was 89 people Boya Village community consists of 34 workers, 25 merchants and 30 members of the public. Overall samples taken by each group is determined by the formula of proportional allocation technique (Riduan, 2004) .Teknik data analysis in this study using nonparametric statistical analysis, namely by presenting results of surveys and questionnaires on the perception of respondents. Then to prove the hypothesis that after revitalization study Donggala port area are improving the welfare of the surrounding community, used descriptive statistical analysis with the Wilcoxon Signed-Rank test by using SPSS for Windows version 16. These results indicate that: (1) Revitalization of the Port area Donggala began in 2014, with the rehabilitation and restoration of institutional and physical prevervasi significant impact on the development of the region, it can be seen from the indicators: Income, Infrastructure, Transport (2) Revitalization of the Port area of Donggala effective in promoting the welfare of the surrounding community. There are significant differences between categories of income, employment and transport. (3) The income of people increased after the revitalization of the port, but a decline in revenue after deducting the Consumer Price Index (CPI). This decrease is caused, by the role and function of the port is still not optimal (4) The number of workers accommodated in TKBM Cooperative Donggala port is not currently increasing. This happens because of Donggala port is still not operate properly (5) From the analysis Wilcoxon Signed-Rank impact of the revitalization of the Donggala port to the welfare of the surrounding community, it can be seen from the indicators of people's income and the development of infrastructure and transport modes.